Remarks for Opening Plenary of the High Level Segment - COP10 - Zoellick, Robert B. (World Bank, Washington, DC, 2018)
Robert B. Zoellick, President of the World Bank Group, discussed four topics: (i) why focus on biodiversity; (ii) World Bank Group investment in biodiversity; (iii) who should be focusing on biodiversity; and (iv) how we value the wealth of biodiversity.